Autologous hematopoietic cell transplantation in multiple sclerosis. (2nd January 2017) - Bell, Simon M.; Sharrack, Basil; Snowden, John A.
ABSTRACT: Introduction: Autologous haematopoietic cell transplantation (AHCT) is an evolving treatment avenue in multiple sclerosis (MS), which may be highly effective in controlling disease activity and improving disability. However, AHCT is associated with intrinsic toxicities and risks compared with conventional therapies. With growing experience in patient selection and treatment delivery, AHCT is increasingly considered an option in patients with aggressive disease that's responding poorly to disease modifying therapy. Areas covered: This article provides an introduction to AHCT and looks at its development as a treatment for MS over the last 20 years. It also highlights potential mechanisms of action, patient selection, and future trends for this treatment approach. Expert opinion: Currently published data suggest that AHCT's use is associated with significant reduction in MS disease activity and marked improvement in disability when used in patients with highly active relapsing remitting disease. Its long term safety and efficacy have not been fully evaluated but as increasing clinical trial data are published, its use is likely to grow. Further randomised controlled studies are needed to compare AHCT with standard disease modifying therapies and to optimise transplant regimens. Mechanistic studies may provide potential markers for response and a better understanding of disease pathogenesis.